2018
DOI: 10.3748/wjg.v24.i15.1591
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition status andHelicobacter pyloriinfection in patients receiving hemodialysis

Abstract: Chronic kidney disease (CKD) patients receiving hemodialysis (HD) often develop gastrointestinal abnormalities over their long treatment period. In general, prognosis in such patients is poor due to the development of protein-energy wasting (PEW). Therefore, it is important to clarify the etiology of PEW and to establish better strategies to deal with this condition. Chronic Helicobacter pylori (H. pylori) infection in the gastric mucosa has a close association with not only the development of peptic ulcer dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 95 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…The important question is how useful the eradication therapy of H. pylori can be in patients with CKD. In a recent study by Sugimoto et al23 they concluded that, since patients with CKD have a higher risk of gastroduodenal diseases, all hemodialysis patients are advised to use endoscopic examinations and H. pylori eradication therapies. In a study by Hsu et al31 on pre-ESRD patients and matched patients on ESRD, they concluded that early H. pylori eradication has a lower risk of peptic ulcer bleeding in positive H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The important question is how useful the eradication therapy of H. pylori can be in patients with CKD. In a recent study by Sugimoto et al23 they concluded that, since patients with CKD have a higher risk of gastroduodenal diseases, all hemodialysis patients are advised to use endoscopic examinations and H. pylori eradication therapies. In a study by Hsu et al31 on pre-ESRD patients and matched patients on ESRD, they concluded that early H. pylori eradication has a lower risk of peptic ulcer bleeding in positive H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…The role of H. pylori eradication therapies in improving the nutritional status of patients with CKD has also been studied. Some studies have shown that infection with H. pylori in CKD patients is associated with malnutrition, and it is recommended that eradication of H. pylori may improve nutritional status 23,32. In a pilot study,32 the effect of H. pylori eradication therapy on nutritional status in H. pylori positive hemodialysis patients was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result emphasizes the possible link between PEW and altered immune function and an increased risk of infection, as already mentioned in previous studies. 24,25 The main strengths of the present study are the total number of patients included and the long follow-up period. We also analyzed a sample of patients from several dialysis units located in different geographical areas of the country.…”
Section: Discussionmentioning
confidence: 99%
“…[14] This induces a decrease in serum proteins and causes alterations in nutritional indices, weight loss, and loss of muscle mass. [15]…”
Section: Discussionmentioning
confidence: 99%